α-Glucosidase Inhibitory and A Leptospermone Derivative from Rhodomyrtus tomentosa - Ferlinahayati Ferlinahayati; Daniel Alfarado; Eliza Eliza; Budi Untari (Indonesian Journal of Chemistry, 2020)
One of the treatments for diabetes mellitus disease is to control blood sugar level using an inhibitor of α-glucosidase enzyme. The methanol extracts of the fruit, stem, and leaves of Rhodomyrtus tomentosa were found significant in inhibiting α-glucosidase with an IC50 value of 20.57, 20.36 and 43.99 μg/mL respectively. The ethyl acetate and n-butanol fractions from the methanol extract of R. tomentosa fruit exhibited the potent inhibition (IC50 13.49 and 19.29 μg/mL) compare to acarbose and n-hexane fraction (IC50 383.68 and 1175.16 μg/mL). A leptospermone derivative, rhodomyrtosone D, was isolated from the ethyl acetate fraction of R. tomentosa fruit. The structure of rhodomyrtosone D was identified based on spectroscopic analysis, as well as comparing with literature data. The α-glucosidase inhibition of rhodomyrtosone D (IC50 110.45 μg/mL) was 3.5 fold more potent than acarbose. Thus, R. tomentosa plant could be potential as a natural resource of α-glucosidase inhibitor.